Fundamental uncertainty, portfolio choice, and liquidity preference theory - Markus Pasche (Kiel Institute for the World Economy (IfW), 2009)
One of Keynes' core issues in his liquidity preference theory is how fundamental uncertainty affects the propensity to hold money as a liquid asset. The paper critically assesses various formal representations of fundamental uncertainty and provides an argument for a more bounded rational approach to portfolio choice between liquidity and risky assets. The choice is made on the basis of individual beliefs which are subject to mental representations of the underlying economic structure. Self-consciousness arises when the agent is aware of the fact that beliefs are dispersed among agents due to the absence of a “true” model. Responding to this fact by increasing liquidity preference is rationalized by the higher ex post performance of choice. Moreover, we analyze the case that the portfolio is partially financed by debt. It is explored how fundamental uncertainty affects the volume of the portfolio and hence money and credit demand as well as the probability of debt failures.
Keywords: G11; D81; E41; B31; 330; Liquidity preference; portfolio choice; self-confidence; self-consciousness; fundamental uncertainty; bounded rationality; Keynes; Knight; Liquiditätspräferenz; Entscheidung bei Unsicherheit; Beschränkte Rationalität; Portfolio-Management; Wechselkurs; Theorie